Position dependence of the 13 C chemical shifts of α‐helical model peptides. Fingerprint of the 20 naturally occurring amino acids - Vila, Jorge Alberto (2004)
The position dependence of the 13C chemical shifts was investigated at the density functional level for -helical model peptides represented by the sequence Ac-(Ala)i -X-(Ala)j -NH2, where X represents any of the 20 naturally occurring amino acids, with 0 i 8 and i + j 8. Adoption of the locally dense basis approach for the quantum chemical calculations enabled us to reduce the length of the chemical-shift calculations while maintaining good accuracy of the results. For the 20 naturally occurring amino acids in -helices, there is (1) significant variability of the computed 13C shielding as a function of both the guest residue (X) and the position along the sequence; for example, at the N terminus, the 13C and 13C shieldings exhibit a uniform pattern of variation with respect to both the central or the C-terminal positions; (2) good agreement between computed and observed 13C and 13C chemical shifts in the interior of the helix, with correlation coefficients of 0.98 and 0.99, respectively; for 13C chemical shifts, computed in the middle of the helix, only five residues, namely Asn, Asp, Ser, Thr, and Leu, exhibit chemical shifts beyond the observed standard deviation; and (3) better agreement for four of these residues (Asn, Asp, Ser, and Thr) only for the computed values of the 13C chemical shifts at the N terminus. The results indicate that 13C , but not 13C , chemical shifts are sensitive enough to reflect the propensities of some amino acids for specific positions within an -helix, relative to the N and C termini of peptides and proteins.